Neonatal pleural empyema caused by emm type 6 group A streptococcus. Issue 4 (5th August 2013) - Nohara, Fumikatsu; Nagaya, Ken; Asai, Hiroko; Tsuchida, Etsushi; Okamoto, Toshio; Hayashi, Tokitsugi; Sakata, Hiroshi; Terao, Yutaka; Azuma, Hiroshi
Abstract: Since the mid‐1980s, there have been increasing reports of severe invasive group A streptococcal (GAS) disease in children and adults. There are few reports, however, of neonatal invasive disease, particularly neonatal pleural empyema caused by GAS. Although many mechanisms have been reported for the pathophysiology of invasive GAS infections, similar reports for neonates were unable to be located. Reported herein is the case of a 3‐day‐old girl with pleural empyema caused by GAS that demonstrated a high invasive capacity for human epithelial cells.